Exemplification in academic discourse structure - Kucelman, Ewa (LingBaW. Linguistics Beyond and Within, 2016)
The study examines the role that exemplification plays in academic discourse. As the latest approaches emphasize, discourse is an interactional activity involving as participants both the writer and the reader. In order to ensure the proper understanding of his/her message, writers make use of different discourse strategies such as reformulation, specification, generalization or elaboration. We focus on how exemplification, viewed as the satellite, contributes to the better recognition of the subject matter, which is understood as the nucleus. In the first two sections of the study, we present an overview of discourse relations which call for the use of constructions applied in exemplification. The second part, which is based on the linguistic material obtained from a close scrutiny of two classic articles from the field of linguistics and one linguistic textbook, is devoted to the description of how exemplification contributes to specification and elaboration. We try to find and describe the specific relations, for example set-member, whole-part, process-step and object-attribute which hold between the nucleus and the satellite. Finally, we attempt at listing discourse areas which call for exemplification. The study illustrates that what are known as separate discourse relations are in fact closely related.